Frailty, depression and anxiety in later life. - KENNY, ROSE ANNE; LAWLOR, BRIAN; NI MHAOLAIN, AINE; ROMERO-ORTUNO, ROMAN (My University, 2012)
Background: Anxiety and depression are common in older people but are often missed; to improve detection we must focus on those elderly people at risk. Frailty is a geriatric syndrome inferring increased risk of poor outcomes. Our objective was to explore the relationship between frailty and clinically significant anxiety and depression in later life. Methods: This study had a cross-sectional design and involved the assessment of 567 community-dwelling people aged ?60 years recruited from the Technology Research for Independent Living (TRIL) Clinic, Dublin. Frailty was measured using the Fried biological syndrome model; depressive symptoms were assessed using the Center for Epidemiological Studies Depression Scale; and anxiety symptoms measured using the Hospital Anxiety and Depression Scale. Results: Higher depression and anxiety scores were identified in both pre-frail and frail groups compared to robust elders (three-way factorial ANOVA, p ?0.0001). In a logistic regression model the odds ratio for frailty showed a significantly higher likelihood of clinically meaningful depressive and anxiety symptoms even controlling for age, gender and a history of depression or anxiety requiring pharmacotherapy (OR = 4.3; 95% CI 1.5, 11.9; p = 0.005; OR = 4.36; 95% CI 1.4, 13.8; p = 0.013 respectively). Conclusions: Our findings suggest that even at the earliest stage of pre-frailty, there is an association with increased symptoms of emotional distress; once frailty develops there is a higher likelihood of clinically significant depression and anxiety. Frailty may be relevant in identifying older people at risk of deteriorating mental health.
PUBLISHED
PMID: 22333477
Keywords: frailty, anxiety, depression, elderly; frailty, anxiety, depression, elderly